Cost-effectiveness analysis of robotic-arm assisted total knee arthroplasty (TKA) versus conventional TKA in Iranian population - Zahra Goudazi; Mojtaba Jafari; Abdollah Kiyaei; Ramin Ravangard; Seyed Ali Hashemi; Khosro Keshavarz (Health Economics Review)
Abstract Objective The costs of robot-assisted surgery are high compared to traditional surgeries, the main objective of this study is to investigate the cost-effectiveness of robotic total knee arthroplasty (rTKA) and manual total knee arthroplasty (mTKA) in Iran. Method The economic evaluation carried out from the perspective of the healthcare system used patients aged 64 years and older in Markov models. A cohort of 10,000 patients receiving either rTKA or mTKA was simulated using a Markov model. The time horizon of the study was lifetime and the model cycles were considered to be annual. From the literature and Iranian experts, transition probabilities, costs, and utility values were extracted. The incremental cost-effectiveness ratio (ICER) was also calculated. The evaluator was willing to pay ppp$ 16,153 for each quality-adjusted life year (QALY) gained. Sensitivity analyses were performed to test the robustness of the uncertainties of the model’s variables. Results A base case analysis showed the rTKA strategy to be more costly ($18,599) than the mTKA strategy ($16,804), with an associated greater effectiveness of 9.20 versus 9.05 QALYs. The value of the incremental cost-effectiveness ratio (ICER) of rTKA in contrast to mTKA stood at $12,037 per QALY with a follow-up duration of 16 years, which is within the bounds of the threshold value of $16,153 per QALY set in Iran. In the probabilistic sensitivity analysis, there was a 90% probability that rTKA would be found cost-effective in comparison to mTKA. Conclusion In conclusion, this study finds that rTKA may be cost-effective than traditional methods in the context of Iran, especially as its value comes to be appreciated.